First report of pediatric ehrlichiosis in Mexico - Daniela Cisneros-Saldaña; Luis E. Osuna- Álvarez; José I. Castillo-Bejarano; Abiel H. Mascareñas-De los Santos; Denisse N. Vaquera-Aparicio; Samantha Pérez-Cavazos (Permanyer, 2023)
Background: Ehrlichia chaffeensis is responsible for most cases of human ehrlichiosis, an acute febrile tick-borne disease. This clinical entity is more commonly reported in adults from the United States. Therefore, it is of special interest to characterize this disease in children, given that very few cases in children have been reported outside of this country. Case report: We describe the case of a 15-year-old female from northeastern Mexico with a five-day history of myalgias, arthralgias, fever, abdominal pain, rash, and somnolence. The possibility of tick-borne disease was suspected considering that she lived with three tick-infested dogs that had recently died and a neighbor with similar symptoms who deteriorated rapidly and died a week earlier. Ehrlichia spp. was detected in blood samples by polymerase chain reaction. The patient completed a sevenday course of doxycycline and was discharged with complete resolution of symptoms. Conclusions: This case is the first report of ehrlichiosis in a pediatric patient in Mexico, illustrating the importance of considering tick-borne diseases as a differential diagnosis in patients with rash, fever, and altered level of consciousness. This initial clinical presentation may be indistinct from other conditions such as dengue, meningococcemia, and multisystem inflammatory syndrome in children (MIS-C), among others.